Corpo - Eau’Rageuses; Catarina Fernandes (Glad!, 2016)
Discover the feminist band Eau’Rageuses and their poem ‘Corpo’, written by Catarina Fernandes and set to music by Eau’Rageuses. You can listen to the track and read the lyrics both in Portuguese and in a French translation. Another track by Eau’Rageuses will be released with GLAD!’s next issue!